EFFECTIVENESS OF SPORTS GAME METHODS ON FINE MOTOR DEVELOPMENT OF EARLY CHILDHOOD AT HIDAYAH GRENDEN PUGER KINDERGARTEN - Anisfiyah, Nafisah; Angraeny Unedia Rachman; Asti Bhawika Adwitiya (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
The golden age period in children is very important for a child's life in the future, this is the basis for teaching children cognitive, motor, social, and language skills. Fine motor development at an early age will be beneficial now and in the future. Children who have poor fine motor coordination or who do not develop perfectly tend to experience frustration, failure, and rejection. Fine motor skills are basic skills that need to be built at an early age . Learning while exercising can help children improve coordination and fine motor skills. This study is to determine the effectiveness of the sports game method on the development of fine motor skills in early childhood . The Study case literature review method is practiced in this writing. Children's fine motor skills were measured using sports game techniques on two respondents who received intervention; the data was then evaluated three times, namely in the first week; second; and fourth. The results of the observations were carried out for four weeks. Observations were conducted before and after the intervention. The results of observations after the intervention showed an increase in the ability and development of children's fine motor skills. The conclusion is that the method of playing sports effectively improves fine motor skills in early childhood , it is hoped that parents and teachers can apply sports game techniques both at home and at school.